2013
DOI: 10.2214/ajr.12.8986
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Iterative Reconstruction Versus Adaptive Statistical Iterative Reconstruction and Filtered Back Projection in Liver 64-MDCT: Focal Lesion Detection, Lesion Conspicuity, and Image Noise

Abstract: OBJECTIVE The purpose of this study is to compare three CT image reconstruction algorithms for liver lesion detection and appearance, subjective lesion conspicuity, and measured noise. MATERIALS AND METHODS Thirty-six patients with known liver lesions were scanned with a routine clinical three-phase CT protocol using a weight-based noise index of 30 or 36. Image data from each phase were reconstructed with filtered back projection (FBP), adaptive statistical iterative reconstruction (ASIR), and model-based i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 15 publications
1
48
0
Order By: Relevance
“…[1][2][3]5,6 In this study, overall image quality in neck CT examinations was improved with MBIR, potentially allowing the exchange of improved image quality for further radiation-dose reduction. A recent study applying MBIR to chest CT reported radiation-dose reductions approaching 70%-80%.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[1][2][3]5,6 In this study, overall image quality in neck CT examinations was improved with MBIR, potentially allowing the exchange of improved image quality for further radiation-dose reduction. A recent study applying MBIR to chest CT reported radiation-dose reductions approaching 70%-80%.…”
Section: Discussionmentioning
confidence: 96%
“…Both phantom and clinical studies have confirmed that the application of the MBIR algorithm results in an improved contrast-to-noise ratio (CNR), lower background noise (BN), [1][2][3][4] and reduction of helical conebeam artifacts. 2,4 Clinical studies in the delineation of arteries in the posterior fossa on 3D brain CT angiography, 1 improved liver lesion detection, 3,5 general evaluation of abdominopelvic CT, 2 and pediatric chest CT 6 all support the use of MBIR, with or without radiation-dose reduction.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…These include iterative reconstruction models such as adaptive statistical iterative reconstruction and model-based iterative reconstruction. [9][10][11][12][13][14][32][33][34][35][36][37][38][39][40] Although these imaging algorithms provide an additional method for dose reduction in CT-guided procedures, their availability is currently limited to newer CT scanners for routine diagnostic CT imaging. The greater availability of the iterative reconstruction software over time may allow for increased operator comfort when evaluating low-dose images during CT-guided procedures, potentially further reducing the radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric patients and patients who receive multiple scans for acute disease follow-up, chronic conditions, and screening purposes often undergo CT with modified scanning protocols to reduce dose. [9][10][11][12][13][14] This type of protocol modification has also been used in CT-guided interventions to limit radiation dose when performing multiple scans during the procedure. 8,[15][16][17][18] Given the increased desire to reduce radiation dose to patients, we transitioned our protocols for CT-guided spine biopsies to use a lower dose.…”
mentioning
confidence: 99%